2009
DOI: 10.1166/jnn.2009.1311
|View full text |Cite
|
Sign up to set email alerts
|

Early Growth of Nano-Sized Calcium Phosphate on Phosphorylated Bacterial Cellulose Nanofibers

Abstract: It is believed that studies on the early hydroxyapatite (HAp) deposition on nano-sized substrates may possibly allow us to understand the formation mechanisms of biominerals at the molecular level. In this study, bacterial cellulose (BC) nanofibers were phosphorylated and used as nano-sized templates for early mineralization of calcium phosphate (Ca-P). To initiate mineralization the BC nanofibers were immersed in 1.5 times simulated body fluids (1.5 SBF) at 37 degreees C for varying periods of time. The depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Similarly, Nge et al declared that the initial precursor of HAP on BC was OCP [24]. However, to the best knowledge of the authors, none of the previous studies regarding Ca-P formation on BC nanofibers [21,22,24,26,38,39] has observed the formation of ACP and TCP probably due to the fact that such techniques as XRD and SEM are unable to capture the information of nascent Ca-P deposits. It is believed that studies on the early Ca-P formation on nano-sized substrates may possibly allow us to understand the formation mechanisms of biominerals at the molecular level [26] and thus enable us to develop synthetic biomaterials which would resemble natural ones more closely.…”
Section: Xanes Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, Nge et al declared that the initial precursor of HAP on BC was OCP [24]. However, to the best knowledge of the authors, none of the previous studies regarding Ca-P formation on BC nanofibers [21,22,24,26,38,39] has observed the formation of ACP and TCP probably due to the fact that such techniques as XRD and SEM are unable to capture the information of nascent Ca-P deposits. It is believed that studies on the early Ca-P formation on nano-sized substrates may possibly allow us to understand the formation mechanisms of biominerals at the molecular level [26] and thus enable us to develop synthetic biomaterials which would resemble natural ones more closely.…”
Section: Xanes Analysismentioning
confidence: 99%
“…To this end, Ca-P formation on pristine and surface-modified BC nanofibers has been reported by using conventional techniques such as XRD, TEM, and FTIR [19][20][21][22][23][24][25]. For many years, it has been believed that octacalcium phosphate (OCP) is the precursor of hydroxyapatite (HAP) on BC nanofibers regardless of surface nature [24,26]. However, that finding is inconsistent with the common notion that amorphous calcium phosphate (ACP) is the first-formed solid Ca-P phase which evolves into crystalline phases [13,27,28] and that the surface nature of templates can significantly alter the nucleation and transformation of the mineralizing crystals [29][30][31].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 2 more Smart Citations
“…Other biomaterials used to improve the biocompatibility of BC include starch [22,47], hydroxyapatite [12,16,48,49,50,51,52], poly(vinyl alcohol) [53,54,55], poly(methyl methacrylate) [56] and polyacrylamide [57]. …”
Section: Improvement Of Biocompatibility Of Bc Structuresmentioning
confidence: 99%